Penerapan Sistem Pre-Order dalam Pemasaran Komoditi Hortikultura Cabai (Studi Kasus pada Pasar Sub Terminal Agribisnis Baturiti di Kecamatan Baturiti, Kabupaten Tabanan) - SARDI, ANTONIUS JULIAN ARIE; SUSRUSA, KETUT BUDI; ANGGRENI, I. G. A. A. LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Application of Pre-Order System in Marketing of Chili Horticultural Commodities The agricultural sector has an important role in the Indonesian economy. One of the agricultural sub-sectors that is needed in daily life in relation to cooking spices is chili ( Capsicum annum L ). Chili is very much needed so it should always be available in sufficient quantities and at an affordable price.The purpose of this study: (1) to find out the pre-order system applied at Pasar STA Baturiti, Tabanan Regency, (2) to know the marketing channels for chili horticultural commodities and farmer's share in marketing the pre-order system at Pasar STA Baturiti, Baturiti District, Tabanan Regency. This research is descriptive qualitative. This research was conducted at Pasar STA Baturiti, Baturiti District, Tabanan Regency. This research is secondary data. Data collection was done by interview method and documentation method. Respondents in this study were farmers and collectors of chili horticultural commodities in Pasar STA Baturiti. This research has found that the pre-order system in purchasing chili can be implemented by having to meet the related requirements and conditions. These terms and conditions include: farmers and buyers have a good relationship and trust each other, farmers have the ability to fulfill orders that have been placed by buyers, and there is an agreement that binds both parties, including: the number of chilies ordered, the time the chili is delivered, the quality , prices and terms of payment. Marketing channels play an important role in the chili sales process so that it reaches consumers. There are two types of chili marketing channels at Pasar STA Baturiti. The channels are Farmers – Pre-order traders – Retailers – consumers  and Farmers – Wholesalers – Retailers - consumers. Sales with a pre-order system provide acceptance for farmers at the ideal farmer's share level. The percentage of farmer's share in this study was 82.97%.